Role of echogenic foci in ultrasonographic risk stratification of thyroid nodules: Echogenic focus scoring in the American College of Radiology Thyroid Imaging Reporting and Data System - Li, Renxu; Liang, Zhenwei; Wang, Xiangyu; Chen, Luzeng (Frontiers in Oncology, 2022)
Background: Although echogenic foci may raise malignancy rates in thyroid nodules, the association between peripheral calcification or macrocalcification and thyroid carcinoma is controversial. We evaluated the malignancy probability of various echogenic foci and explored whether the method of determining a thyroid nodule’s points score in the echogenic foci category of the American College of Radiology (ACR) Thyroid Imaging Reporting & Data System (TI-RADS) is reasonable. Methods: We retrospectively evaluated 819 patients with 852 nodules. The patterns of echogenic foci on ultrasonography were classified into the following four categories: punctate echogenic foci, macrocalcification, peripheral calcification, and multiple different types of echogenic foci. The core needle biopsy results were divided into two groups: benign, and malignant or suspicious for malignancy. Results: Among the 852 nodules, 471 (55.3%) had echogenic foci on ultrasonography. Of these nodules, there was no significant statistical difference in the malignant or suspicious for malignancy rate between nodules with peripheral calcification and those with macrocalcification (40.0% [8/20 vs. 30.6% [11/36], respectively; p = 0.474). The incidence of malignancy or suspicious for malignancy for nodules with peripheral calcification, macrocalcification, or multiple different types of echogenic foci was significantly lower than the incidence for punctate echogenic foci alone, with odds ratios of 0.265 (95% confidence interval (CI): 0.105–0.667; p = 0.005), 0.175 (95% CI: 0.083–0.368; p = 0.000), and 0.256 (95% CI: 0.136–0.482; p = 0.000), respectively. Conclusion: We found no significant statistical difference for the risk of malignancy or suspicious for malignancy rate between peripheral calcification and macrocalcification in thyroid nodules. We observed that nodules with multiple different types of echogenic foci were not associated with higher malignant or suspicious for malignancy rates compared with nodules with punctate echogenic foci alone.